Theoretical insights into chemical recycling of polyethylene terephthalate (PET) - Conroy, Stuart; Zhang, Xiaolei (Polymer degradation and stability, 2024)
•Mechanistic and kinetic studies of PET chemical recycling methods are discussed.•Various approaches towards a PET circular economy are discussed and compared.•Catalytic glycolysis with the synergistic mechanism is the most promising approach.•Novel techniques, e.g. microwave heating, heterogeneous catalysts, should be studied. Polyethylene Terephthalate (PET) is one of the most commonly used plastics. Currently, PET waste has been mainly recycled through mechanical methods and alternative effective ways have emerged, such as chemical recycling including ammonolysis, aminolysis, hydrolysis, alcoholysis and glycolysis. However, a precise understanding of the reaction mechanisms and kinetics of these methods is lacking. This paper aims at providing a comprehensive review elucidating the mechanisms and the reaction kinetics of these methods, considering various catalysts, solvents and heating modes. The degradation performance of each method and its suitability towards a circular economy is discussed and compared. It is concluded that novel processes of PET glycolysis stand out as the most promising chemical recycling methods. The degradation process via glycolysis can be significantly enhanced by the increased interactions facilitated by the synergic effect reaction mechanism, and the improved kinetics provided by the advanced heating modes such as microwave-assisted techniques. Heterogeneous catalysts with large surface area were found to promote efficient PET degradation into its monomer, Bis(2-Hydroxyethyl) terephthalate (BHET); these catalysts also offer environmental and economic advantages owing to their ease of separation and reusability. This review provides a guidance for future research aimed at designing an effective PET chemical recycling process. It was identified that to advance PET glycolysis in the near future, research can focus on 1) the utilising novel heterogeneous catalysts and catalyst supports that induce synergic effect reaction mechanisms, and 2) advancing technologies such as microwave heating. Furthermore, the suitability of PET recycling technologies should be considered in the context of high BHET yield/selectivity, mild reaction conditions, short reaction times and reusability, and economical feasibility at an industrial scale.